2013
DOI: 10.1111/vco.12069
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin versus alternating carboplatin and doxorubicin for the adjuvant treatment of canine appendicular osteosarcoma: a randomized, phaseIIItrial

Abstract: Despite numerous published studies describing adjuvant chemotherapy for canine appendicular osteosarcoma, there is no consensus as to the optimal chemotherapy protocol. The purpose of this study was to determine whether either of two protocols would be associated with longer disease-free interval (DFI) in dogs with appendicular osteosarcoma following amputation. Dogs with histologically confirmed appendicular osteosarcoma that were free of gross metastases and underwent amputation were eligible for enrollment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 20 publications
7
75
0
5
Order By: Relevance
“…Adjuvant chemotherapy, using doxorubicin and/or either carboplatin or cisplatin can extend survival somewhat. Prescription patterns have shifted over the decades but recent comparisons of chemotherapy regimens concluded that 6 doses of carboplatin was less toxic (and in one study somewhat more effective) than doxorubicin or combination treatments. However, only 15% of canine osteosarcoma patients treated with surgery plus optimal chemotherapy protocols survive for more than 3 years …”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant chemotherapy, using doxorubicin and/or either carboplatin or cisplatin can extend survival somewhat. Prescription patterns have shifted over the decades but recent comparisons of chemotherapy regimens concluded that 6 doses of carboplatin was less toxic (and in one study somewhat more effective) than doxorubicin or combination treatments. However, only 15% of canine osteosarcoma patients treated with surgery plus optimal chemotherapy protocols survive for more than 3 years …”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of the immune microenvironment in pulmonary metastatic cOSA is necessary to develop immunotherapeutic strategies targeting this site of disease, since the majority of dogs succumb to pulmonary metastases even after amputation and adjuvant cytotoxic chemotherapy . While direct sampling of metastatic lesions would ideally be evaluated to provide the most representative impression of the metastatic immune microenvironment, the invasiveness of collecting cOSA pulmonary metastases from dogs in a clinical setting often precludes this.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin is a platinum chemotherapeutic agent that is used to systemically treat a variety of tumors in companion animals, such as osteosarcoma and apocrine gland adenocarcinoma of the anal sac (AGASACA) (Ross, 1991;Bennett, 2002;Emms, 2005;Saam, 2011; Simcock, 2012;Selmic, 2014;Kozicki, 2015;Skorupski, 2016;Wouda, 2016) and has been shown to be stable in poloxamer carriers (Exner 2005;Hsu, 2014) and fully release carboplatin (Risselada, 2016) however information is not available about the stability of the combination of carboplatin and poloxamer gel in vivo and its release profile.…”
Section: Introductionmentioning
confidence: 99%